Patterns of Clean and Alternative Energy Utilization in Khlong Sam Subdistrict, Khlong Luang District, Pathum Thani Province - Kertsup, Natta; Hadda, Wirasak; Siriworasakul, Wanida; Klommeung , Patcharee; Amnuay , Rawikarn (Dhammathas Academic Journal, 2026)
This study aimed to: (1) examine clean and alternative energy sources suitable for reducing environmental pollution and lowering the operational costs of Khlong Sam Subdistrict Administrative Organization; (2) analyze the investment feasibility of implementing such energy sources; and (3) develop an appropriate clean and alternative energy utilization plan for Khlong Sam Subdistrict Administrative Organization. A mixed-methods research design was employed. Quantitative data were collected from 399 residents in Khlong Sam Subdistrict using a questionnaire and analyzed using frequency, percentage, mean, and standard deviation. Qualitative data were obtained from 30 key informants, comprising executives of Khlong Sam Subdistrict Administrative Organization, personnel involved in energy management, and community leaders or representatives. In-depth interviews and focus group discussions were used as research instruments, and qualitative data were analyzed through inductive interpretation. The findings revealed that: 1. Solar energy was identified as the most suitable alternative energy source, followed by hydropower, wind energy, biomass energy, and geothermal energy, respectively. Respondents demonstrated a high level of awareness regarding energy conservation and environmental protection (x̄ = 4.11, S.D. = 1.03), and perceived the Subdistrict Administrative Organization’s capacity for energy management to be at a high level (x̄ = 4.32, S.D. = 0.776). 2. Investment feasibility was also rated at a high level (x̄ = 4.33, S.D. = 0.823). Key approaches included the installation of solar photovoltaic systems, the promotion of collaboration among communities and relevant agencies, and implementation in accordance with government regulations. 3. The proposed clean and alternative energy utilization plan emphasized solar energy as the primary source. The plan consists of assessing local energy potential, developing supporting infrastructure, determining investment models, implementing pilot projects, and establishing a clean energy learning center. These measures are expected to enhance public participation, reduce energy expenditures, and support sustainable local development.